Factors Influencing Bond Rating Predictions - Carolina, Cyntia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to identify the factors that influence bond rating predictions, with the research variables limited to: 1) to examine the effect of profitability on bond ratings for manufacturing companies listed on the Indonesia Stock Exchange (IDX); 2) to examine the effect of liquidity on bond ratings for manufacturing companies listed on the IDX; 3) to examine the effect of cash flow on bond ratings for manufacturing companies listed on the IDX; and 4) to examine the simultaneous effect of profitability, liquidity, and cash flow on bond ratings for manufacturing companies listed on the IDX. The research findings are as follows: 1) Profitability has an impact on bond ratings for manufacturing companies in the goods and consumption sector from 2020 to 2022; 2) Liquidity has an impact on bond ratings for manufacturing companies in the goods and consumption sector from 2020 to 2022; 3) Cash flow has an impact on bond ratings for manufacturing companies in the goods and consumption sector from 2020 to 2022; 4) Simultaneously, profitability, liquidity, and cash flow have an impact on bond ratings for manufacturing companies in the goods and consumption sector from 2020 to 2022, with a combined effect of 82.5%.